2011
DOI: 10.1007/s00134-011-2351-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effects of two humidifier systems on endotracheal tube resistance

Abstract: We did not find differences between the two types of humidifiers in terms of airflow resistance during prolonged mechanical ventilation when the devices were selected on the basis of individual clinical needs. The increase in resistive load is physiologically relevant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 36 publications
(69 reference statements)
0
18
0
Order By: Relevance
“…Another study based on ETT air flow resistance after extubation showed that ETT narrowing was associated with the duration of ventilation, without statistical differences between 2 humidifier devices. 27 Shah and Kollef 28 found a 10% intraluminal volume loss increased with prolonged tracheal intubation, even if measurements were performed up to 5 d after extubation. In a subsequent study, Wilson et al 29 showed a large degree of resistance, occurring in all sizes of ETT, unpredictable regarding the duration of intubation, and beginning immediately in some subjects.…”
Section: Discussionmentioning
confidence: 97%
“…Another study based on ETT air flow resistance after extubation showed that ETT narrowing was associated with the duration of ventilation, without statistical differences between 2 humidifier devices. 27 Shah and Kollef 28 found a 10% intraluminal volume loss increased with prolonged tracheal intubation, even if measurements were performed up to 5 d after extubation. In a subsequent study, Wilson et al 29 showed a large degree of resistance, occurring in all sizes of ETT, unpredictable regarding the duration of intubation, and beginning immediately in some subjects.…”
Section: Discussionmentioning
confidence: 97%
“…inspissated secretions, others) increases airflow resistance and thus the effort to breathe. Data indicate that the airflow resistance of endotracheal tubes at the time of extubation is much higher than at the time of intubation, thus increasing the respiratory muscle work 15 . The optimal duration of the SBT trial is at least 30 minutes and no more than 120 minutes.…”
Section: Weaning Processmentioning
confidence: 98%
“…The deterioration in respiratory system mechanics in patients who fail the weaning trial is characterized by an increase in intrinsic positive end-expiratory pressure (PEEP), and inspiratory resistance with a decrease in dynamic lung compliance 22 . Physicians must take into account that the components of the ventilator circuit, including endotracheal tubes (size, deposit of secretions, curvatures, humidifiers), can increase resistance to airflow and the resistive component of the work of breathing in patients breathing spontaneously 15,23 .…”
Section: Respiratory Pump Failurementioning
confidence: 99%
“…3 A recent study by Moran et al showed that endotracheal tube resistance increased by 53% after a mean of 10 days of mechanical ventilation. 4 This study included 22 patients with heat and moisture exchangers (HMEs) and 22 patients with heated humidifier, and similar increases in resistance were present in both groups, demonstrating that, even with the latest generations of heated humidifiers and HMEs, optimal humidification may not be attained.…”
mentioning
confidence: 89%
“…3 Its other limitation is that it is somewhat cumbersome and is intended only for research. Considering that optimal humidity is still not provided to mechanically ventilated patients, 4 reliable surrogates of humidity should be developed. We are still looking for simple techniques to measure humidity during daily practice.…”
Section: See the Original Studies On Pages 1442 And 1449mentioning
confidence: 99%